Shinella lacus sp. nov., a novel microcystin-degrading alphaproteobacterium containing the bla carbapenemase gene. Issue 11 (10th November 2022) - Gong, Zhi-Lian; Deng, Yang; Jiang, Zhu-Ming; Liu, Lu-Qing; Yu, Li-Yan; Su, Jing; Zhang, Yu-Qin
Abstract : A Gram-stain-negative, rod-shaped, microcystin-degrading bacterium, designated as CPCC 100929 T, was isolated from a fresh water reservoir in Sichuan Province, PR China. This isolate grew well at 4–37 °C and pH 6.0–8.0, with optimal growth at 28–32 °C and pH 7.0, respectively. The major cellular fatty acids were C18:1 ω7 c /C18:1 ω6 c, C16:0, C18:1 ω7 c 11-methyl and C19:0 cyclo ω8 c . The predominant respiratory quinone was Q-10. Diphosphatidylglycerol, phosphatidylglycerol, phosphatidylethanolamine, phosphatidylmethylethanolamine and phosphatidylcholine were detected in the polar lipids extraction. The 16S rRNA gene sequence of strain CPCC 100929 T was closely related to those of members of the genus Shinella, with the highest similarity of 98.6 % to Shinella zoogloeoides DSM 287 T and 97.4–98.4 % with other identified Shinella members. In the phylogenetic trees based on 16S rRNA gene sequences and the core-genes analysis, strain CPCC 100929 T was included within the clade of the genus Shinella . The values of average nucleotide identity (81.4–86.7 %) and digital DNA–DNA hybridization (25.4–44.6 %) between strain CPCC 100929 T and other Shinella species were all below the thresholds for bacterial species delineation, respectively. The genomic DNA G+C content of strain CPCC 100929 T was 63.6 %. The genomic sequence analysis indicated that this species contained genes encoding peroxidase, bla carbapenemase and the key enzyme for microcystin bio degradation, as well as rich carbohydrate-active enzyme coding genes, which might endow the micro-organism with properties to adapt to diverse environments. Based on its phenotypic and genetic properties, we propose that strain CPCC 100929 T (=T1A350 T =KCTC 72957 T ) is the type strain of a novel species with the name Shinella lacus sp. nov.